2020
DOI: 10.1038/s41598-020-68900-8
|View full text |Cite
|
Sign up to set email alerts
|

Long-term bowel dysfunction following low anterior resection

Abstract: Study aimed to assess long-term bowel function in patients who underwent low anterior resection for cancer five and more years ago. Patients who underwent low anterior resection for rectal cancer from 2010 to 2015 at National Cancer Institute were prospectively included in our study. They were interviewed using low anterior resection syndrome (LARS) score and Wexner questionnaire. We also assessed possible risk factors of postoperative bowel disorder. 150 patients were included in our study. Of them 125 (83.3%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 19 publications
4
25
0
Order By: Relevance
“…[19][20][21] On the other hand, preoperative radiation therapy is recommended for patients with advanced rectal cancer in Western countries, and it has been reported that the radiation therapy also leads to defecation disorders. [13,22] The incidence of major LARS after rectal cancer surgery has been reported to be more than 40% [22][23][24], and the incidence of major LARS was similar in this study.…”
Section: Discussionsupporting
confidence: 76%
“…[19][20][21] On the other hand, preoperative radiation therapy is recommended for patients with advanced rectal cancer in Western countries, and it has been reported that the radiation therapy also leads to defecation disorders. [13,22] The incidence of major LARS after rectal cancer surgery has been reported to be more than 40% [22][23][24], and the incidence of major LARS was similar in this study.…”
Section: Discussionsupporting
confidence: 76%
“…However, some complications may occur after radiotherapy, including rectal anastomotic leakage, anastomotic stenosis, and proctitis. Dulskas et al included patients who had received rectal cancer resection at the National Cancer Institute of Lithuania from 2010 to 2015, and found that preoperative chemoradiotherapy was confirmed to be a risk factor for postoperative defecation changes, which was similar to the results of many previous studies (28). Sun et al also showed that long-course neoadjuvant radiation, along with low anastomosis, are likely independent risk factors for postoperative bowel function and quality of life (QOL) (29).…”
Section: Discussionmentioning
confidence: 59%
“…This is obvious with quality of life, which is negatively affected, while period caring the ileostomy. The different scenario is with the bowel function, as our and other authors’ results showed that LARS is a long-term issue, without any significant change in a timeline [ 32 , 33 , 34 , 35 , 36 , 37 ]. In addition, we did not evaluate sexual and urinary functions that are also important parts of quality of life.…”
Section: Discussionmentioning
confidence: 81%